2022
DOI: 10.21608/ejhm.2022.248721
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Intercellular Adhesion Molecule-1 and TNF- in Patients with COVID-19 and Its Relation to Disease Severity

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a major health concern and can be devastating, especially for the elderly. It causes a systemic inflammatory response, involving dysregulation and misexpression of many inflammatory cytokines.Objectives: To assess the cytokine profile in COVID-19 patients and detect its relation with disease severity. Patients and methods:This study included 50 COVID-19 patients confirmed by reverse transcription-polymerase chain reaction (RT-PCR), of whom 20 with severe pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ramadan et al investigated the cytokine profile in patients with COVID-19 and found a correlation between it and the severity of the disease as determined by the CO-RADS score. They discovered that the level of intercellular adhesion molecule 1 and CO-RADS score were significantly positively correlated [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramadan et al investigated the cytokine profile in patients with COVID-19 and found a correlation between it and the severity of the disease as determined by the CO-RADS score. They discovered that the level of intercellular adhesion molecule 1 and CO-RADS score were significantly positively correlated [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Covid-19, ED (a hallmark of the disease) and activation of adhesion molecules trigger the progression of immunothrombosis and the development of critical complications (Bonaventura et al 2021 ; Al-kuraishy et al 2020a , b). The increasing level of ICAM-1, GDF-15, and YKL-40 is associated with poor clinical outcomes in Covid-19 patients (Babalghith Al-kuraishy et al 2022a , b; Ramadan et al 2022 ; Sharma et al 2020 ). Of note, Covid-19 leads to the induction of fibrotic remodeling secondary to lobar micro-ischemia with the development of fibrotic interstitial changes.…”
Section: Tirzepatide and Covid-19mentioning
confidence: 99%